Augmented Reality of Rasulullah SAW Traces in Receiving the Revelation of The Qur'an - Samsudin Samsudin; Ilka Zufria; Triase Triase (STMIK Budi Darma, 2022)
Al-Qur'an is the holy book of Muslims whose information is eternal and has miracles that can always be proven by the progress of science and technology that is fast and powerful. The Qur'anic revelation revealed to the Prophet Muhammad for about 23 years left a long, special footprint in the cities of Mecca and Medina. In this Centennial era, some Muslims were preoccupied with technological advances which sometimes led to the neglect of the Qur'an. So that the crisis of knowledge of generations of Muslims about the footsteps of the Prophet Muhammad in receiving the revelation of the Qur'an is very little, This is very dangerous for the unity of Muslims. So that with technological advances we also attract the interest of young people to learn the Qur'an. Augmented Reality technology with the Marker-based tracking method utilizes Qr Code and the use of agile development methods and design using UML so that application developers can produce Augmented Reality applications that can show traces of the decline of the Qur'an in Mecca and Medina. The appearance of Mecca and Medina in the form of 3 dimensions along with asbabunnuzul information causes interest and ease for someone to study the verses of the Qur'an. It is hoped that this application helps to facilitate the generation of Islam in learning and understanding ayat of the Qur'an.